AB0676 Efficacy of rituximab therapy against anti-neutrophil cytoplasmic antibody-related hypertrophic pachymeningitis: a case series. (12th June 2018) - Kobayashi, K.; Nakagomi, D.; Hanai, S.; Yamagata, M.; Sugiyama, T.; Kawashima, H.; Hiraguri, M.; Kasuya, T.; Furuta, S.; Ikeda, K.; Nakajima, H.; Kitamura, K.
Abstract : Background: Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis presents with various symptoms. ANCA-associated hypertrophic pachymeningitis (HP) is a very rare pathology. Objectives: This study aimed to investigate the efficacy of rituximab (RTX) against patients with ANCA-related HP. Methods: Seven patients were identified by retrospective chart review from local registries at four Hospitals in Japan. All patients met Chapel Hill 2012 Consensus Conference definitions of ANCA–associated vasculitis and were complicated with HP. We assessed the dose of prednisolone, CRP, and MRI findings of HP before and after RTX administration. Results: Three female and 4 male were evaluated. Median age was 66 years-old. Four cases had HP at the onset of vasculitis. Relapse of HP before RTX administration was found in 2 cases. RTX was used as an initial treatment in one patient. Daily dose of prednisolone and CRP were significantly decreased from baseline levels 24 weeks after RTX treatment. Evaluation of HP by contrast MRI showed improvement in six of seven cases. No relapse after RTX treatment was observed during the follow-up period of 24 weeks. Severe adverse effects were not found in any patients. Conclusions: Our case series highlight the efficacy of RTX against patients with difficult-to-treat ANCA-related HP. Future studies in this context in a prospective manner are definitely required to establish the B-cell depletion therapy by RTX as a treatment option for ANCA-related HP. References: [1] Shimojima Y, Kishida D, Hineno A, et al. Hypertrophic pachymeningitis is a characteristic manifestation of granulomatosis with polyangiitis: A retrospective study of anti-neutrophil cytoplasmic antibody-associated vasculitis. Int J Rheum Dis2017;20:489–496. [2] Aman S, Susheel K, Ajay W, et al. Successful treatment of hypertrophic pachymeningitis in refractory Wegener's granulomatosis with rituximab. Clin Rheumatol2010;29:107–110. Disclosure of Interest: None declared